(untitled) (LACCEI, 2024)
The main objective of this research was to determine the most relevant impact on the implementation of Environmental Management Systems (EMS) in agribusiness worldwide according to the most recent published research work. For this, the methodology of systematic literature review was used, considering IOP Science, Proquest and Scopus databases, and information search strategies under inclusion and exclusion criteria. The results obtained were 38 articles, in which the impacts derived from the application of environmental management systems in agro-industrial activity were evidenced, identifying economic, environmental, and social impacts and published research by country, among which Indonesia, Brazil, Colombia and Greece stand out. It is concluded that the most relevant impact in the environmental field was the reduction and control of emissions, effluents, waste, as well as the reduction of the use of agrochemicals including pesticides and fertilizers in the economic field, the increase in revenues was reported due to the opening of global markets and an increase in product sales prices, reducing energy consumption and reducing waste losses, improving productivity, as well as reducing expenses due to the application of sanctions due to environmental accidents, waste treatment in the social sphere, it is reported that recycling practices are adopted, awareness and improvement of the knowledge and skills of stakeholders for environmental care and protection.